VISUALIZATION BASED ON COMPUTER METHODS FOR PROCESSING INFORMATION - Zh.E. Kenzhebayeva , (Academic Journal of Physical and Chemical Sciences, 2019)
Human-centered visualization of information requires reliable and appropriate user research that improves the system or confirms its benefits. New methods, information visualization approaches are usually evaluated by taking a lot of time and money, if they constitute minimal resources, this leads to results that may be invalid. If, the number of participants is usually limited and does not allow to get a reliable assumption about the results. Thus, performance indicators play a key role in the visualization of information, the existing web survey tools are not convenient. In this article, the authors present new ways to evaluate information visualization systems via the Internet. In general, the visualization of information plays an important role in ensuring the possibility of data assimilation and the transformation of raw information into actionable ideas.